Risk assessment in poisoning with special reference to odollam and organophosphorous compounds - Tergestina, Meenu M.; Simon, Sunitha (International Journal of Research in Medical Sciences, 2017)
Background: Poisoning with organophosphorous compounds, odollam and other substances are common. Affected persons present with a wide variety of clinical features. Prognostic indicators of high mortality are important for management and to decide on intensive care unit admission. Methods: Admissions due to poisonings from April 2015 to March 2016 were assessed. The clinical features, electrocardiographic changes and laboratory investigations of 915 patients were obtained and statistically analysed. Results: The most commonly ingested poisons were odollam (26%) and organophosphorous compounds (22%). The overall mortality was 22%. Mortality was highest in organophosphorus compounds (38%) and odollam (33%) compared to other causes. Hyperkalemia, low systolic blood pressure, consumption of poison in powder or paste form, delayed presentation, bradycardia and extensive chest signs correlated with mortality in odollam and organophosphorous compound poisoning. Conclusions: Poisoning with odollam or organophosphorous compounds is an increasingly common life threatening condition. Markers of mortality identified in this study were incorporated into a simple scale for assessment of risk, namely the PoPPER scale: potassium level >5.5 mE/L, systolic blood pressure <90 mmHg, paste/powder form of poison ingestion, extremely late presentation, rate of QRS <40/min or impending respiratory paralysis.